‘Guidance' or ‘Misleading'? The government subsidy and the choice of enterprise innovation strategy - Ding, Jian; Wang, Jiaxin; Liu, Baoliu; Peng, Lin (Frontiers in Psychology, 2022)
The effectiveness of a company's innovation efforts is influenced by its innovation strategy, which is an important component of the industry's overall high-quality development. A dynamic evolutionary game is used to study the impact of the government-enterprise game relationship and the firm-competitor game relationship on firms' green innovation behavior, based on an analysis of the cost-benefit differences between the government and enterprises under various strategies. Because the marginal funds produced by the organization's innovation effort have a direct impact on the game's outcome, the results suggest that the organization's innovation strategy is focused on maximizing individual benefits. There are two game equilibria, and both the firm's and its competitors' innovation capacities influence the firm's innovation strategy. Green subsidies from the government encourage subsidized businesses to try new things, but they may unintentionally drive away non-subsidized competitors. The degree of penalty (the effectiveness with which the government subsidy policy is applied), the marginal profit of the subsidised firms in using the government subsidies, and the decision of the rivals' strategies are all factors that have a direct impact on the game's outcome. This study provides a theoretical framework for improving the efficacy of government subsidies while encouraging market innovation.